التدخين وباء اجتماعي دراسة اجتماعية ميدانية (Journal Of Educational and Psychological Researches, 2011)
The main purpose of this study is to investigate the relationship between smoking and increased risk if diseases.   It has been estimated that gland of smoker in the world 3.1 billion smoker . Glands an estimated 4.1 million deaths per day . The proportion of death in developing countries 70% due to relationship between poverty and smoking .    The damage caused by smoking not only no the Alzbn users , but to millions of people around them .    According to medical studies to confirm the relationship between forced smoking and increased risk of heart diseases , lung cancer , and mental diseases . it is surprising that some workers in the medical profession and health using tobacco in front of their patients .      The Researchers selected vendor sample of (50) smokers women . The results of study is  ( 6%) single and (14%) married and ( 54%) widows and (26%) Divorced (20%) smoke due to Limitation(50%) Psychological shock (30%) offected by friends (50%) elimination (20%) elimination of nervus . (30%) give the smoker feel for rest  , (60%) smoking in the public place (40%) smoking securetly .